Neuroinflammation in Prion Diseases: Concepts and Targets for Therapeutic Intervention - Riemer, Constanze; Gultner, Sandra; Heise, Ines; Holtkamp, Nikola; Baier, Michael (CNS & Neurological Disorders - Drug Targets, 2009)
Prion infections of the central nervous system (CNS) are characterized by a reactive gliosis and the subsequent degeneration of neuronal tissue. The activation of glial cells, which precedes neuronal death, is likely to be initially caused by the deposition of misfolded, in part proteinase K-resistant, isoforms (termed PrPTSE) of the normal cellular prion protein (PrPc) in the brain. Proinflammatory cytokines and chemokines released by PrPTSE-activated glial cells and stressed neurons may contribute directly or indirectly to the disease development by enhancement and generalization of the gliosis and via cytotoxicity for neurons. Recent studies have illustrated that interfering with inflammatory responses may represent a therapeutic approach to slow down the course of disease development. Hence, a better understanding of driving factors in neuroinflammation may well contribute to the development of improved strategies for treatment of prion diseases.